Re-description of Craspodema reflectans (Nematoda, Cyatholaimidae) using confocal laser scanning microscopy - Semprucci, Federica; Burattini, Sabrina (Zootaxa, 2015)
Craspodema reflectans, erected by Gerlach 1964, is here re-described from some specimens recently found in the Maldivian archipelago and the implication of the new findings for the taxonomy of the Craspodema genus is discussed. Accordingly, an emended diagnosis of Craspodema genus and C. reflectans species are proposed. New data are also provided with the aid of the confocal laser scanning microscopy, using the natural fluorescence of the nematodes. The approach described here lays new foundations for the study of Museum collection material and it may be decisive for capture of new morphological details.